A study of correlation between seismicity and mental health: Crete, 2008–2010 - G.C. Anagnostopoulos; M. Basta; Z. Stefanakis; V.G. Vassiliadis; A.N. Vgontzas; A.G. Rigas; S.T. Koutsomitros; S.J. Baloyannis; G. Papadopoulos (Geomatics, Natural Hazards & Risk, 2015)
We compared the number of M > 2 earthquakes in an area, including the island of Crete, Greece, to the number of admissions to the Psychiatric Inpatient Unit of the University of Crete (IPU/UoC), during the period 2008–2010. We found that when earthquakes with M 6.4 occurred in the region examined, the number of monthly admissions to the Acute Care Unit of the IPU/UoC, NAA, reached lowest values, whereas this number increased when the monthly number NE of small (M < 3) earthquakes increased. We also found a positive correlation between the total number of monthly admissions NA and NE (r = 0.601/P = 0.001). When a daily resolution analysis was performed for the month with the highest value of NE, we found that an abrupt increase in the number of small earthquakes was followed by an increase in the number of admissions after ∼2 days (during that month, from a total of 71 patients, 38/10 people were diagnosed with schizophrenia/bipolar disorder). We hypothesize that seismic activity might be a significant contributing factor influencing the frequency of admissions of psychotic disorders in Crete in the period 2008–2010 and that the beneficial/adverse effects are related to the anomalous electric field/extra low frequency–ultra low frequency emissions.